Clinical, parasitological and socioeconomic evaluation of children attended in the pediatrics of the community Nosso Lar- vergel do Lago, Maceió-Alagoas - Ferro, Renata Marcela Cavalcante Ferreira; Silvestre, Maria Eduarda Ramos; Almeida, Ana Carolina Medeiros de; Oliveira, Gilsan Aparecida de; Bezerra, Emanuel Felipe Marques; Moura, Livia Lorena Santos; Silva, Maria Karoline Gomes (Seven Editora, 2023)
School-age children comprise a group with a greater propensity to exposure in contaminated environments, which favors the involvement of pathologies caused by geohelminths. Therefore, the present study aims to verify the clinical and socioeconomic changes associated with infection by parasitosis in children. This is a cross-sectional observational study to verify the clinical, parasitological and socioeconomic alterations of children attended in the pediatrics of the community our home, located in the neighborhood Vergel do Lago, Maceió-AL. It was found among the samples of biological material that 20.4% were positive for gastrointestinal helminths, of which 66.7% were positive for Ascaris lumbricoides, 22.2% for Ancylostoma duodenalis and 11.1% for Hymenolepis diminuta, as well as that 39% of the children ingest water from the tap, 42.8% do not have the habit of sanitizing their hands before meals and more than half do not have basic sanitation in their Residences. It was also observed that most mothers had incomplete elementary education and most had an income of up to 1 minimum wage. Thus, it is concluded that sanitation and hygiene conditions contributed to the number of positives. The prevalence of Ascaris lumbricóides suggests low adherence to the habit of hand hygiene by children. Most of them lived with about seven people and in a rented house, with low income, evidencing their precarious socioeconomic level. In addition, the mothers’ low level of education predisposes them to significant resistance to return with the stool sample. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-147